SYSTEMATIC LITERATURE REVIEW PEMANFAATAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN - Arwanto, Moch Miftah Mawardi; Priati Assiroj; Cakra Trinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Augmented Reality (AR) is a technological advancement that can be utilized as an interactive learning medium by visualizing objects in three dimensions to enhance material comprehension. This study aims to identify methods, AR design software, and various applications of AR as different media. Using the PRISMA method, 28 selected articles were analyzed. The findings indicate that Marker-based Tracking is the dominant method compared to Markerless Tracking. The most commonly used AR design software is Unity, often combined with Vuforia. In terms of AR applications, the highest usage is found in the field of science, followed by several other fields. This study demonstrates that AR has great potential if continuously developed and can be utilized across various fields, not just in education.